Young entrepreneurs and non-teleological temporality in Portugal and the UK. (February 2020) - Holdsworth, Clare; Mendonça, Marina
The promotion of young enterprise is central to European Union youth policy, particularly since the financial crisis of 2007/2008. Expectations that young people need to be enterprising and eschew dependency on formal structures of salaried employment are a key narrative in European and national youth policies. These policy initiatives correspond with recent theoretical development of the entrepreneurial self as a managerial version of the governable individual. Endorsements of entrepreneurship implicitly promote a normative expectation that young people's future orientations need to be innovative, flexible and creative. There is, therefore, an implicit temporality to youth entrepreneurship. This paper's contribution to scholarship on how young lives are promoted and produced as entrepreneurial selves is to document how young people's engagement with entrepreneurship fosters orientations to present and future. Conventionally entrepreneurs are assumed to be goal-orientated. In our qualitative study of young entrepreneurs in two European countries (n = 28), we find that this assumption of goal-orientation needs qualification. Young entrepreneurs in our study engage with the idea that being an entrepreneur is about being creative rather than seeking to maximise financial profit. Their focus on creativity, innovation and problem-solving is realised through a non-teleological commitment to what they are doing in the here and now, rather than calibrating their activities in relation to predetermined goals and worrying about the possibility of future failure.